Conditions for The Development of Pedagogical Competencies of Students in The Educational Process - Aliev Islambek Tursinbaevich (European International Journal of Pedagogics, 2025)
The article analyzes the didactic conditions that serve to develop students' pedagogical competencies, analyzes the conditions aimed at improving the quality of pedagogical education and improving the process of training future teachers, studies the content and methods of forming pedagogical competencies, interrelated and integrative formation of knowledge, skills and personal characteristics in education, combination of theoretical knowledge with practice, development of professional qualifications and communicative abilities, formation of personal and ethical qualities, theoretical knowledge, practical skills, personal-psychological and ethical qualities, which are the main components of pedagogical competencies, special attention to each component of the educational process, all organizational, methodological and material-technical factors necessary for the development of students' pedagogical competencies in the educational process, clear definition of content and learning goals, implementation of interactive and active teaching technologies, comprehensive organization of pedagogical practice, constructive dialogue between teachers and students, mechanisms of reflection and self-assessment, educational tools and innovative issues of technology implementation are interpreted.